2007
DOI: 10.1080/00071660701341971
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soy isoflavones on egg quality and bone mineralisation during the late laying period of quail

Abstract: 1. Soy isoflavones play a role in calcium and bone metabolism. Poor egg quality, skeletal abnormalities and architectural deterioration of bone tissue are common problems under hot climate conditions and with increased age in poultry. 2. In this study, we investigated the effects of soy isoflavone supplementation on egg production, egg quality, bone mineral density (BMD), levels of osteocalcin (OC), vitamin D, calcium (Ca), phosphorus (P) and alkaline phosphatase (ALP) activity in quail (Coturnix coturnix japo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 38 publications
4
23
2
Order By: Relevance
“…This result is in agreement with the results of the study by Ni et al (2007) on daidzein in which daidzein supplement significantly increased the eggshell thickness, and decreased the percentage of cracked eggs. Sahin et al(2007) also found that soy isoflavone supplementation could significantly improve bone mineral density, serum osteocalcin, vitamin D, calcium, phosphorus levels and alkaline phosphatase activity in quail during the late laying period.…”
Section: Egg Qualitymentioning
confidence: 98%
“…This result is in agreement with the results of the study by Ni et al (2007) on daidzein in which daidzein supplement significantly increased the eggshell thickness, and decreased the percentage of cracked eggs. Sahin et al(2007) also found that soy isoflavone supplementation could significantly improve bone mineral density, serum osteocalcin, vitamin D, calcium, phosphorus levels and alkaline phosphatase activity in quail during the late laying period.…”
Section: Egg Qualitymentioning
confidence: 98%
“…The extent of bone mineralization affects bone strength [2] and poor mineralization leads to increased risk of fractures [3]. Skeletal abnormalities and architectural deterioration of bone tissue are common under hot climatic conditions because a high environmental temperature leads to more excretion of minerals like calcium, iron, zinc and lower retention rates of minerals like calcium, phosphorus, sodium, manganese, copper and zinc resulting in decreased bone strength of broilers [4][5][6][7].Heat stress has deleterious effects on the skeletal system by decreasing length and widths of tibia, and by promoting mineralization which in turn reduces bone strength [8]. Rapid growth followed by high nutrient intake with energy high diet alone can cause severe lameness, bone defects, and deformity [9].…”
mentioning
confidence: 99%
“…Calcium absorption is increased by CoQ10 supplementation [11,12]. The dietary antioxidant supplementation decreased the mineral excretion in hot climatic condition in broilers [4]. CoQ10 is a lipophilic antioxidant and its supplement reduces the oxidative stress and increased the enzymatic antioxidant activity [13].…”
mentioning
confidence: 99%
“…In addition, Sahin et al (2007) reported that dietary ISF improved feed intake, egg production and egg quality in heat stressed quail, but the effects were not observed for those raised under thermo-neutral environment. Hence, those observations may be attributed to antioxidative effects rather than estrogenic effects of ISF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that inclusion of FSB in diets of broiler chicken (Feng et al, 2007a;Mathivanan et al, 2006), Japanese quail (Chah et al, 1976), and neonatal pig (Zamora and Veum, 1988) improved ADG and FE. Recent studies (Jiang et al, 2007;Sahin et al, 2007) have shown that the antioxidant and estrogenic activity of isoflavones (ISF) improved animal performance after animals were given FSB. As antioxidants, ISF may also pro-tect low density lipoprotein (LDL) from oxidation (Wei et al, 1995) and may exert its anti-atherogenic effects (Anthony et al, 1995).…”
Section: Introductionmentioning
confidence: 99%